Quee(Re)appropriations and sovereign art statements in the work of Kent Monkman - Livingston, Susan Briana (DEU, 2019)
Kent Monkman is a First Nations artist who employs a number of strategies that I term quee(re)appropriations. Quee(re)appropriations are a specific form of reappropriation, a form that challenges the heteronormativity of dominant hegemony and highlights the confrontational and direct nature of the reclamation in the form of re-appropriation. Queer, here an adjective, describes practices that explicitly create alternatives to dominant culture. Historically, appropriation, seizure and confiscation have been used by conquerors as tools of empire, often through the field of anthropology under the guise of documentation and preservation. The seemingly documentarian collection of indigenous images and culture, selectively appropriated by colonial powers, have been used to justify a hierarchical power structure that led to expansion, relocation and genocide. Monkman uses quee(re)appropriation, or the queer re-appropriation of images previously appropriated by colonial powers, to shift the power structure and challenge hegemony. Quee(re)appropriations enable Monkman to make his own sovereign decolonial and two spirited artistic statements.